Addressing Climate Change: Method, Rationales, and Procedures for Developing Science-Based Policies (BioLaw Journal - Rivista di BioDiritto, 2026)
Summary: 1. Introduction – 2. Mechanisms Underlying the Selection of Scientific Knowledge Required to Adopt Policies to Combat Climate Change – 3. Role and Functioning of Scientific Advisory Systems Serving Legislators and Government Bodies – 4. Civil Society Participation in Public Decision-Making Processes – 5. Power Relations in Managing the Climate Crisis – 6. Conclusions